The Assays of Bacteria-Yeast Consortia as Probiotics Candidates and Their Influences on Nutrients Utilization of Quails Diet - A. Sofyan; R. S. H. Martin; E. B. Laconi; A. Jayanegara; H. Julendra; E. Damayanti; A. E. Suryani (Tropical Animal Science Journal, 2019)
This study aimed to assay L. plantarum (P1), S. cerevisiae (P2), and its combination (P3) as probiotics candidates and their effects on nutrient digestibility in Japanese quails (Cortunix cortunix japonica) diets. In vitro assays were employed to evaluate the antibacterial activities against pathogenic bacteria (Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Salmonella pullorum), sensitivity to antibiotics (i.e., streptomycin, penicillin, and erythromycin), stress on bile salt and acidity condition. Evaluation of probiotics on in vivo nutrient utilization was carried out by administration of probiotics to laying quails in drinking water with various treatments (R0, control; R1, L. plantarum; R2, S. cerevisiae; R3, combination of R1+R2; R4, commercial feed additive). Results showed that the highest inhibitory activity was performed by P2 on S. aureus (17.28 mm). Treatments P2 and P3 were resistant to all the tested antibiotics, while P1 was resistant to streptomycin and penicillin. P1 was tolerant to bile salts whereas P2 was tolerant to gastric acidity conditions. For the in vivo experiment, quails fed R1, R2, and R4 had higher nitrogen retention as compared to R0 (p<0.05). However, all treatments revealed similar metabolizable energy values. The cluster analysis showed that quails consuming the combination of L. plantarum and S. cerevisiae were within the same cluster with the control but different clusters from the individual probiotics across all parameters, indicating a possible antagonistic effect between the two species.  In conclusion, the inclusion of L. plantarum or S. cerevisiae inhibits pathogenic bacteria without influencing nutrient utilization of quail diet.